BS EN 2467. Aerospace series. Steel X2CrNi18-9 (1.4307). Air melted. Softened. Plates, sheets and strips. 0, 4 mm ≤ a ≤ 20 mm. 520 MPa ≤ Rm ≤ 670 MPa. (10th September 2020) - British Standards Institution,
No abstract available